Perbandingan vigoritas benih Acacia mangium hasil pemuliaan dan yang belum dimuliakan - Naning Yuniarti; M Zanzibar; Megawati; Budi Leksono (Foresty Faculty of Hasanuddin University, 2014)
Seeds with high vigour are seeds that can germinate normally in sub-optimum conditions and above normal in optimum condition. To predict the performance of seedlings after planting and the storability of seeds, it is necessary to test the seed vigour. This study aims to investigate the growth and storage vigour of Acacia mangium breeding and unbreeding seeds. The experiment design was arranged in completely randomized design with each treatment being replicated four times with 100 seeds. Results obtained showed that breeding seeds had better growth and storage vigour.